OPTIMASI FORMULASI SEDIAAN HANDBODY LOTION EKSTRAK DAUN TEH HIJAU (Camellia sinensis Linn) - S Slamet; Waznah U (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2019)
The aim of this experimentis optimizing the preparation of hand body lotion from tea leaf extract. Some compositions were chosen which were previously oriented to get good preparation consistency. The method used by mixing part A which consists of cetil alcohol, lanolin, stearic acid heated to 700c, and part B consists of glycerol, triethanolamine, paraben metal and aquadest which were also heated at the same temperature, then stirred until homogeneous and tea leaf extract was added. Then, the hand body lotion produced was tested.The test results of handbody lotion showed a stable preparation from testing for 3 weeks with a semi-solid form, green colour, aroma of tea, and homogenity, pH of preparation 7, dispersion test : 2.8 x3.1 cm2 - 7x8 cm2, adhesion test : 0.73 seconds - 02.3 seconds. The result of irritation test showedthat the hand body lotion is safe or non-irritating in 10 respondents. Theconclusion of this experiment is the hand body lotion produced is safe according to the requirements.